Prognostic Value of Lactate Dehydrogenase in Advanced Esophageal Squamous Cell Carcinoma Patients with Immunotherapy - Yan LI, Kunlun WANG, Hui YANG, Erjiang ZHAO, Bingxu LI, Shenglei LI, Xiaotao DONG, Ling YUAN (Zhongguo quanke yixue, 2022)
Background The overall efficacy of immunotherapy is unsatisfactory in patients with advanced esophageal squamous cell carcinoma (ESCC) , since only a few cases could obtain benefits from the therapy. Therefore, it is of great importance to select effective prognostic indicators. Objective To investigate the prognostic value of lactate dehydrogenase (LDH) in advanced ESCC patients with immunotherapy. Methods This study enrolled patients diagnosed with advanced ESCC by pathological and imaging examinations in Henan Cancer Hospital from October 2016 to October 2019. Data were collected, including baseline data obtained from the electronic medical record system, LDH level at the 8th week of immunotherapy, and results〔containing death, disease remission, progression-free survival (PFS) and overall survival (OS) 〕 of a follow-up until August 31, 2021. Log-rank test was used to compare Kaplan-Meier curves of PFS and OS by baseline LDH. Multivariate Cox regression analysis was used to analyze the potential factors associated with PFS and OS. Results Of the 44 cases enrolled, a higher objective response rate was found in those with lower baseline LDH (n=28, baseline LDH<200 U/L) instead of those with higher baseline LDH (n=16, baseline LDH≥200 U/L) (χ2=8.522, P=0.013) . Eight patients with disease progression (PD) had higher ?LDH than 36 patients without PD (t=2.394, P=0.021) . At the end of follow-up, 9 patients (20.5%) survived, with a median PFS of 6 (2, 11) months, and a median OS of 11 (7, 18) months. PFS was significantly different in those with higher and lower baseline LDH levels (χ2=6.790, P=0.009) . OS was also significantly different in those with higher and lower baseline LDH levels (χ2=12.327, P<0.001) . The baseline LDH〔HR=2.686, 95%CI (1.274, 5.664) , P=0.009〕was associated with the PFS after immuotherapy. And the multivariate analyses showed that baseline LDH〔HR=17.440, 95%CI (2.254, 134.962) , P=0.001〕, hemoglobin〔HR=0.005, 95%CI (<0.001, 0.120) , P=0.001〕, monocyte count〔HR=0.066, 95%CI (0.008, 0.525) , P=0.010〕were associated with the OS after immunotherapy (P<0.05) . Conclusion Baseline LDH may be used as a prognostic marker after immunotherapy in patients with advanced ESCC, and a lower baseline LDH may be associated with longer PFS and OS.